Unpacking the Effect of Flipped Learning to Enhance EFL Learners’ Sociopragmatics Knowledge: Speech Acts of Refusals in Focus - Retnaningsih, Woro; Triana, Yunika; Nugroho, Arif (Institut Agama Islam Negeri Kudus, 2024)
Although previous studies have acknowledged the significant effect of flipped classrooms in language learning, few research has concerned about its potential impact on EFL learners’ sociopragmatics knowledge. The present study aims to examine the promising role of flipped learning assisted by WhatsApp applications (i.e., WhatsApp-integrated flipped learning) in enhancing EFL learners’ appropriate use of refusals in English. Another objective is to examine EFL learners’ perception of the WhatsApp-integrated flipped learning activity in facilitating the learning process. This study employed a quasi-experimental with pre-test and post-test design of experimental and control groups. The experimental group (N=36) was taught in a WhatsApp-integrated flipped learning, while the control group (N=36) was enrolled in a similar class but did not experience the use of any digital platform. The intervention was conducted in eight meetings, including the process of data collection using Discourse Completion Tests, semi-structured interviews, and a TAM questionnaire. The results revealed that WhatsApp-integrated flipped learning was proven as an effective strategy to enhance EFL learners’ speech acts of refusals, indicated by a significant difference in the post-test scores of the experimental group compared to the control group. They showed positive acceptance toward the use of the WhatsApp application to facilitate flipped classrooms for teaching sociopragmatics. In addition, the semi-structured interview further disclosed that the learners positively perceived WhatsApp-integrated flipped learning activity. Implications for English language teaching and suggestions for future research are further discussed.